2010
DOI: 10.1093/jmedent/47.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Seasonality ofPhlebotomusSand Flies in Cutaneous Leishmaniasis Foci, Judean Desert, Israel

Abstract: The ecology of Phlebotomus sand flies in cutaneous leishmaniasis foci as a result of Leishmania tropica in the Judean Desert was studied. Between 2005 and 2007, >265,000 specimens were trapped outdoors and 1,233 specimens were collected indoors. The catches included Phlebotomus sergenti Parrot, Phlebotomus papatasi (Scopoli), Phlebotomus syriacus Adler & Theodor, and Phlebotomus tobbi Adler & Theodor. P. sergenti, the local vector of Leishmania tropica, comprised 90% of outdoor catches, and relatively few were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
6
16
1
Order By: Relevance
“…sergenti , the vector of zoonotic L. tropica , to congregate in and around their diurnal resting/breeding sites, which are frequently in rocky habitats with caves or boulder mounds inhabited by hyraxes, has been previously documented [21], [35]. In preceding studies performed in Kfar Adumim and elsewhere in Israel, it was shown that Ph.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…sergenti , the vector of zoonotic L. tropica , to congregate in and around their diurnal resting/breeding sites, which are frequently in rocky habitats with caves or boulder mounds inhabited by hyraxes, has been previously documented [21], [35]. In preceding studies performed in Kfar Adumim and elsewhere in Israel, it was shown that Ph.…”
Section: Discussionmentioning
confidence: 98%
“…In preceding studies performed in Kfar Adumim and elsewhere in Israel, it was shown that Ph. sergenti were abundant in caves and rocky slopes but conspicuously absent from nearby homes [19], [21], [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature and humidity are also the main factors impacting the altitudinal structure of sandfly occurrences [16]. It is known that sandflies react very sensitive to wind speed and prefer breeding sites sheltered from wind [17][20]. Beyond that, high wind speed decreases or even excludes flight activity [17], [21].…”
Section: Introductionmentioning
confidence: 99%